Three-dimensional crumpled graphene as an electro-catalyst support for formic acid electro-oxidation. Issue 12 (7th March 2016) - Zhou, Yang; Hu, Xian-Chao; Fan, Qizhe; Wen, He-Rui
Abstract : Three-dimensional crumpled graphene (PRGO) was synthesized from graphene oxide (GO) solution by the spay drying method and employed as the support material for the Pd catalyst. Compared with the commercial Pd/C and Pd/RGO catalysts, the as-prepared Pd/PRGO catalyst exhibits excellent activity and stability towards formic acid electrooxidation. Abstract : Three-dimensional crumpled graphene (PRGO) was synthesized from graphene oxide (GO) solution by the spay drying method and employed as the support material for the Pd catalyst. The as-prepared catalysts were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), tunnel electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). The electro-catalytic activity and stability toward formic acid oxidation were investigated using cyclic voltammetry (CV) and chronoamperometry (CA), which indicated that the Pd/PRGO catalyst exhibits a larger electrochemically active surface area and mass activity as well as higher long term-stability in comparison to the commercial Pd/C and Pd/RGO catalysts. The enhanced catalytic performance is attributed to the high specific surface area of the 3D formation and utilization efficiency of Pd during the oxidation of formic acid.